44.1: Invited Paper: Quantum‐Dot Light‐Emitting Diodes for Next‐Generation Displays. (4th October 2019) - Acharya, Krishna P.; Titov, Alexandre; Hyvonen, Jake; Ying, Chen Y.; Desireddy, Anil; Tang, Eric; Holloway, Paul H.
Abstract : Solution processed electroluminescent displays made with quantum dot emitter is the next‐generation display technology because of high efficiency, wide‐color gamut, low turn‐on voltage, thin form factor, and low manufacturing cost. We have shown highly efficient quantum dot light emitting diode (QLEDs) using colloidal quantum dot as an emitter and zinc oxide nanocrystal as an electron transport layer. Here, we will present red and green QLEDs with external quantum efficiency (EQE) ≥ 20% and blue QLEDs with EQE > 15%. We will also show the performance improvements of QLEDs using short‐time annealing process and using doped zinc oxide nanocrystal.